Autoantibodies in neuromuscular disorders: a review of their utility in clinical practice - Loser, Valentin; Vicino, Alex; Théaudin, Marie (Frontiers in neurology, 2024)
A great proportion of neuromuscular diseases are immune-mediated, included myasthenia gravis, Lambert-Eaton myasthenic syndrome, acute- and chronic-onset autoimmune neuropathies (anti-MAG neuropathy, multifocal motor neuropathy, Guillain-Barré syndromes, chronic inflammatory demyelinating polyradiculoneuropathy, CANDA and autoimmune nodopathies), autoimmune neuronopathies, peripheral nerve hyperexcitability syndromes and idiopathic inflammatory myopathies. The detection of autoantibodies against neuromuscular structures has many diagnostic and therapeutic implications and, over time, allowed a better understanding of the physiopathology of those disorders. In this paper, we will review the main autoantibodies described in neuromuscular diseases and focus on their use in clinical practice.